Command-centric architecture (C2A): Satellite software architecture with a flexible reconfiguration capability. (June 2020) - Nakajima, Shintaro; Takisawa, Junichi; Ikari, Satoshi; Tomooka, Masashi; Aoyanagi, Yoshihide; Funase, Ryu; Nakasuka, Shinichi
Abstract: This study presents a command-centric architecture (C2A), which is a satellite software architecture exhibiting a flexible reconfiguration capability. C2A was developed through the software development period of the Hodoyoshi satellites. C2A is a software architecture that describes all the actions of a spacecraft by commands to ensure that C2A can change the function of a spacecraft without rewriting the memory. By applying C2A to the software of PROCYON, the world's first 50 kg-class interplanetary spacecraft, it has become possible to reduce the development period and reuse some parts of the previous satellites' software. PROCYON's software was successfully reconfigured several times after its launch using the C2A characteristics. Because of this software architecture, it has become possible to develop reliable onboard software (OBS) for satellites in the short term. Highlights: A software architecture for satellites which combines flexible reconfiguration capabilities and reusability is proposed. A major feature of this software architecture is its ability to describe the behavior of the satellite by command. This software architecture realizes shortening of the development period and reconfiguration during operation.